Investigation of renewable polymer composite from waste oil endurance to UV irradiation exposure by using FTIR and UV-VIS - Mat Hassan, Nik Normunira; Shamsudin, Zainon Sharmila; Mohd Rus, Anika Zafiah; Sulong, Nurulsaidatulsyida (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), 2018)
Waste vegetable from palm oil are most abundant biological sources and important raw materials for production of renewable polymer foam (RF) because of their versatility with high possibility to modify the chemical structure of triglycerides and it derivatives. In this study, waste vegetable oil was synthesized and crosslink with polymethane polyphenyl isocyanate, distilled water and titanium dioxide (TiO2) as filler to produce RF and its composites (RFC) by manual casting method. The physical property of RF and RFC were measured endurance to UV irradiation exposure for a period of 1000 hours by FTIR and UV-Vis. The RF shows an increase of yellowing due to formation of highly coloured quinone on photo-oxidation of the MDIbased polymer on UV irradiation exposure. The quinone oxidations products have been identified by combining FTIR measurement and UV-Visible spectroscopy, for example an absorption at 1510 cm-1 in the FTIR spectrum is due to formation of quinone structure that also absorb strongly at the range of 490 nm to 570 nm in UV-Visible spectrum. The increasing of TiO2 content in RF and RFC shows significant increases of absorbance peak and wavelength after UV irradiation exposure. As the loading of TiO2 increased (up to 10 % of monomer weight), the RFC10 shows highest photostability at 10 % of TiO2 loading. Hence, RFC10 has shown no significant or abrupt changes to the functional groups after UV irradiation exposure, allowing it to have a considerably good UV stabilizer to generate better UV protection.